Etika Pengelolaan Konflik dan Disiplin dalam Lembaga Pendidikan - Elsa Dwiyana; Haris Riadi; Aidil Zulkhairi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research aims to examine the ethics of conflict management and discipline in educational institutions through a literature review approach. As a space for social interaction, educational institutions are inseparable from potential conflicts arising from differences in interests, values, and perceptions among individuals. On the other hand, discipline is an essential element in establishing order and supporting the learning process. However, conflict management and disciplinary enforcement that are not grounded in ethics can instead damage the academic climate and trigger new psychological issues within the educational environment. This study employs a descriptive-analytical method, gathering data from various literature sources such as books, scientific journals, and relevant articles. The results indicate that ethics plays a crucial role as a philosophical and practical foundation in conflict management and disciplinary enforcement that is fair, wise, and humane. An ethical approach is capable of fostering constructive conflict resolution through dialogue, while simultaneously shifting the orientation of discipline from mere punishment toward sustainable character building. Consequently, the integration of ethical values into conflict management and discipline serves as the primary key to creating a harmonious, safe, and conducive educational environment for the growth and development of students.